Application of principal component analysis for face recognition based on weighting matrix using Gui Matlab - Y.A. Lesnussa, N.A Melsasail, Z.A Leleury (Universiti Pendidikan Sultan Idris, 2016)
Application of principal component analysis for face recognition based on weighting matrix using Gui Matlab by Y.A. Lesnussa, N.A Melsasail, Z.A Leleury,